Spatial Analysis of Developmental Population Data in Iraq Using Geographic Information Systems - Basher Faisal Alsaadi; Majid Saddam Salim (Indonesian Journal of Geography, 2026)
This study integrates population and socio-economic data into key development indicators, including the Human Development Index (HDI) and its components (income, education, and health), along with population density, poverty, illiteracy, school enrollment, and health service coverage. The objective is to construct a spatial database and assess regional development disparities across Iraqi governorates. A mixed spatial–statistical approach was applied. Statistical analysis was conducted using SPSS, including descriptive statistics, Pearson correlation, multiple linear regression, and cluster analysis to examine relationships among variables and classify governorates into homogeneous development groups. Geographic Information Systems (GIS) using ArcGIS 10.8 were employed to build a spatial database, integrate socio-economic data with administrative boundary maps, and produce thematic maps for spatial visualization of development patterns and disparities. The results reveal significant spatial inequalities in Iraq. Northern governorates show higher levels of development, with HDI reaching 0.73 in Erbil, while central and southern governorates record lower values, down to 0.58 in Muthanna. Strong negative correlations were found between HDI and both poverty and illiteracy, while positive relationships were observed with education and health indicators. The study concludes that integrating GIS with statistical analysis enhances the identification of development gaps and provides a robust evidence base for sustainable spatial planning and policy formulation.Received: 2025-11-02 Revised: 2026-06-12 Accepted: 2026-07-28 Published: 2026-08-05